2017
DOI: 10.1186/s12888-017-1329-8
|View full text |Cite
|
Sign up to set email alerts
|

Experiences, perspectives and priorities of people with schizophrenia spectrum disorders regarding sleep disturbance and its treatment: a qualitative study

Abstract: BackgroundSleep problems are very common in people with schizophrenia spectrum disorders, and impact negatively on functioning and wellbeing. Research regarding interventions to improve sleep in this population has been lacking. Little is known regarding these patient’s perspectives on sleep problems and their treatment, providing very little foundation on which to develop acceptable and patient-centred treatments.MethodsThis study aims to explore perspectives and priorities of participants with schizophrenia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 96 publications
(106 reference statements)
4
61
0
Order By: Relevance
“…For instance, those experiencing sleep as a refuge voiced longing and fighting for it. This concept of sleep as an escape has also been reported in two recent qualitative papers focused on the psychosis and insomnia experience (Faulkner & Bee, ; Waite, Evans et al., ); we found this belief among both those with depression, bipolar and schizophrenia disorders, showing it can transcend diagnosis. Another metaphor was that sleep itself was a struggle and a negative experience, and thus other participants feared and fought against sleep.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For instance, those experiencing sleep as a refuge voiced longing and fighting for it. This concept of sleep as an escape has also been reported in two recent qualitative papers focused on the psychosis and insomnia experience (Faulkner & Bee, ; Waite, Evans et al., ); we found this belief among both those with depression, bipolar and schizophrenia disorders, showing it can transcend diagnosis. Another metaphor was that sleep itself was a struggle and a negative experience, and thus other participants feared and fought against sleep.…”
Section: Discussionsupporting
confidence: 85%
“…Labelling the process of getting to sleep with “fight”, “battle” and other military metaphors may exacerbate bedtime hyperarousal; non‐veterans rarely use similar military terminology (Carey et al., ; Faulkner & Bee, ; Waite, Evans et al., ). Clinicians may want to explore whether such metaphors work against good sleep for some veterans, and help them develop meaningful personal alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…It may be the case that some participants viewed their sleep problems as so intractable as to be untreatable – this attitude has been reported in patients with sleep problems in the context of established psychosis (17). Faulkner and Bee found that patients had pessimistic or neutral views on the likely effectiveness of “talking therapy” as an intervention for sleep problems, although individual components (e.g., stimulus control, increasing daytime activity) were seen as far more likely to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Previous qualitative studies have explored sleep problems in the absence of other mental health problems (16), or specifically in patients with sleep disturbance in the context of severe and enduring psychosis (17, 18). However, these accounts do not explore the specific developmental context of adolescence and early adulthood nor the novel target of addressing sleep as a preventative intervention for those at risk of serious mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, there is evidence that improvement in nightmares can improve well-being and reduce general psychopathology in diverse groups of psychiatric patients, including those with schizophrenia, and that brief psychological interventions that improve sleep are seen as important and very much appreciated by this population [86,87]. Precisely because it is very much appreciated, one can never dismiss the operation of a placebo effect in reports of well-being.…”
Section: Nightmares and Psychosismentioning
confidence: 99%